Analysis of the Challenges in Valuation of Sacred Properties in Enugu State - Oliobi, I. G.; Ugonabo, C. U. (International Journal of Real Estate, 2025)
According to Okoronkwo (2023), a property valuation is an assessment of property value, based on the location, condition and other multiple factors. The valuation of sacred properties which include shrines, churches, grave yards, etc is a specialized valuation that require peculiar professionalism and comes with some challenges. The aim of this study is to analyze the challenges in valuation of sacred properties in Enugu State with the objective of identifying the challenges and assessing their impact in the valuation of sacred properties in the study area. Further to this, a Hypothesis was put forward to be tested that; there is no significant difference in the respondents‘ assessment on challenges in the valuation of sacred properties in Enugu State. The study adopted the descriptive survey research design with a population of 130 comprising 40 professionals in the Enugu State Ministry of Land and urban Development, 40 registered Estate Surveyors and Valuers and 50 natives. The Sample size was determined by successfully assessed respondents comprising 15 Ministry worker, 22 professionals and 23 natives having a total of 60. The adopted research instruments for data collection were questionnaire and oral interview. The data collected were presented in tables and analyzed using mean rankings and one sample t-test. The study revealed that the challenges in the valuation of sacred properties stems from intangible value of cultural, spiritual and emotional value which cannot be easily quantified and the lack of comparable data of previous transaction of sacred properties, sensitive nature of cultural and ethical practices, legal and regulatory complexity among other factors also contribute to the eminent challenge. it was therefore recommended that Estate Surveyors should improve their awareness of the prevailing issues in the study by organizing and attending seminars and workshops, while enlightening the general public, the appropriate authorities as well as upcoming students in the profession on the subject.